PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Satuan Perangkat Kerja Daerah Kabupaten Kampar) - Sonia, Dewi Puspita; Ratnawati, Vince; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this study was to determine the influence of Human Resource Capacity, Utilization of Information Technology, and Government Internal Control System Against Financial Reporting Information Value (Empirical Study in SKPD KamparRegency). The location of object in this research is SKPD Kampar Regency. While the timing of this study was October 2015. The population in this study were all SKPD in Kampar Regency, which amounted 33 SKPD. The sampling used was purposive sampling. Data collection technique used by the author in this study consisted of field research and literature. Methods of analysis using multiple linear regression analysis. The results showed that Human Resources Capacity, Information Technology Utilization, and Government Internal Control System affect the value of Financial Reporting Information.Based onthe calculation,the valueof determination coefficient of0.440.This showsthat the variable Human Resources Capacity, Information TechnologyUtilization, Government Internal Control Systemgivesthe effect of44.00% of the value offinancial reporting information. The remains of66.00% influenced by other variablesthat are notincludedin this study.Keywords: Human Resource Capacity, Utilization of Information Technology, Government Internal Control System and Financial Reporting Information Value